Learning design for teacher-student co-agency in hybrid spaces - Impedovo, Maria Antonietta; Tan, Seng Chee (Revue internationale du CRIRES / CRI_SAS international Journal)

(untitled) (Centre de recherche et d’intervention sur la réussite scolaire, 2023)
This paper reflects on hybrid learning design focusing on co-agency between teachers and students. The research question is: How could learning design with technology leverage the hybridity of the learning environment and teacher and student co-agency for post-pandemic learning? To answer this question, we examine academic publications for related studies to derive possible post-Covid learning design principles to answer the research question. Aligned with the focus of bridging hybridity, we draw on studies involving different emerging technologies from two different contexts: France and Singapore. The implications for hybridity, co-agency, and zone of possibility are analysed. The discussion stresses the virtual, material, and agentic transformation in hybrid learning design for a post-pandemic learning design.